ANALYSIS FACTOR INCIDENCE OF DIARRHEA IN STUDENT OF SDN 1 TRIENGGADENG SUB DISTRICT PIDIE JAYA - Agustian, Rian; Azwar, Eddy; Dharina, Dharina (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2024)
Background: Diarrhea is one of the major health problems among elementary school students, which can affect their attendance and academic performance. This study aims to analyze the factors associated with the incidence of diarrhea in elementary school children. Method: This research is a descriptive-analytic study with a cross-sectional design involving 95 students as samples. Data analysis was conducted using univariate analysis with frequency percentages and bivariate analysis using the chi-square statistical test (p value 0.05). Result: The results showed a significant relationship between the incidence of diarrhea and access to clean water facilities (p value=0.000), the role of health workers (p value=0.001), handwashing behavior (p value=0.001), and consumption of snacks (p value=0.004). Meanwhile, no significant relationship was found between knowledge (p value=0.609) and the role of teachers (p value=0.189) with the incidence of diarrhea among students. Recommendation: There is a need to improve health education, school sanitation, and the involvement of parents and teachers in shaping clean and healthy living behaviors among children. In addition, integrating school health programs (UKS) more actively and conducting regular monitoring of the school environment are also recommended.